Association of Brinkman Index with Airflow Limitation in Active Smokers Using Portable Spirometry at Saketa Primary Health Care Center - Alicia Thessalonica Nata; Susaniwati Susaniwati (Indonesian Health Journal, 2026)
Tobacco-related diseases account for more than seven million deaths globally each year. In Indonesia, approximately 295,043 deaths in 2025 were attributed to tobacco use. Identifying reliable parameters for early detection of pulmonary impairment in smokers, particularly those who are still asymptomatic, is therefore essential. This research aimed to evaluate the association between Brinkman Index score and FEV?% predicted (measured using portable spirometry) among active smokers at Saketa Primary Health Care Center. This cross-sectional study included 40 male active smokers aged ?35 years at Saketa Primary Health Care Center, South Halmahera, selected using a consecutive sampling method. The Brinkman Index score was used as the independent variable, while FEV?% predicted, measured using portable spirometry according to American Thoracic Society standards, was the dependent variable. Data were analysed using Spearman's correlation test. The mean smoking duration was 29.83 ± 8.85 years, with an average cigarette consumption of 17.50 ± 6.88 cigarettes per day. The mean FEV?% predicted was 74.90 ± 5.91%. Analysis using Spearman's correlation showed a strong negative association between Brinkman Index score and FEV?% predicted, which was statistically significant (r = ?0.771; p < 0.001). Scatter plot analysis showed a coefficient of determination of R² = 0.610, indicating that higher Brinkman Index score values were associated with lower FEV?% predicted values among active smokers.